COMMUNITY PARTICIPATION IN REALIZING DEMOCRATIC ELECTIONS IN PAPUA PROVINCE IN THE PERSPECTIVE OF THE GENERAL ELECTION SUPERVISORY BODY - Salesius Jemaru (HERMENEUTIKA : Jurnal Ilmu Hukum, 2023)
This study aims to determine the role of the community in realizing democratic general elections with various indicators in each stage of the 2014 Legislative Election. This research was conducted in Bovel Digoel Regency, Paniai Regency, Yahukimo Regency, Yapen Islands Regency and Keerom Regency. Primary data and secondary data were obtained through documentation studies, observations and interviews with various related parties. The results of the study show the role and participation of the community in the General Election, the role of the community in supervising each stage of the General Election, the role of the community in realizing political rights in the General Election, the influence of local political developments. Meanwhile, the obstacles that affect the participation of the community in the General Election are internal factors including the integrity of election organizers, the synergy of election organizers, adherence and adherence of organizers to the code of ethics, and external factors, namely the intervention of local officials, socialization of election regulations that have not been maximized and the influence of local customs and culture on the electoral system.